PENGARUH MODIFIED AUDIT OPINION TERHADAP BORROWING CASH FLOW DAN INVESTMENT CASH FLOW - Cahyaningrum, Puspita Hardina; Fitriany, Fitriany (UI Scholars Hub, 2013)
This study examines and analyzes the economic consequences of modified audit opinion on borrowing cash flow and investment cash flow. Panel data model was used to observe the research. The sample of this study was 247 companies listed in Indonesia Stock Exchange for the years 2008-2010. The results show that modified audit opinion, except unqualified opinion with explanatory paragraph about going concern, did not affect borrowing cash flow because audit opinion was not the only consideration for granting credit by creditors. Companies receiving modified audit opinion were proven using more operating cash flow for investing shown in investment cash flow, especially companies receiving unqualified opinion with explanatory paragraph about going concern.